The Effect of Workload on Turnover Intention among Health Workers, with Burnout as a Mediator and Work Stress as a Moderator - I Nengah Aristana; I Wayan Edi Arsawan; I Gede Rihayana (LPPM Universitas Terbuka, 2023)
Purpose - This study aimed to determine the effect of workload on turnover intention among health workers during the COVID-19 pandemic, with burnout serving as a mediator and work stress as a moderator. Methodology - This qualitative study collected data from health workers in health facilities in the Klungkung Regency using questionnaires. The data obtained were then examined using SmartPLS 3.2.9. Findings - The results showed that workload did not impact turnover intention, with burnout serving as a mediator. Meanwhile, work stress has not been proven to increase the connection between workload and turnover intent. Originality - This study provided a different perspective based on organizational behavior theory, which described the turnover intention mechanism of health workers.